2015
DOI: 10.1182/blood-2014-03-560540
|View full text |Cite
|
Sign up to set email alerts
|

Assessing complement blockade in patients with paroxysmal nocturnal hemoglobinuria receiving eculizumab

Abstract: Key Points• CH50 activity reflects C5 blockade in PNH patients treated with eculizumab and is directly related to circulating free eculizumab levels.• Both CH50 and free eculizumab level markers look promising for the monitoring of complement blockade in patients with PNH receiving eculizumab.Paroxysmal nocturnal hemoglobinuria (PNH) is characterized by intravascular hemolysis, which is effectively controlled with eculizumab, a humanized monoclonal antibody that binds complement protein 5 (C5). The residual fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
106
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 34 publications
8
106
0
4
Order By: Relevance
“…Recently, Peffault de Latour et al reported the usefulness of a 50% hemolytic complement (CH50) assay for assessing the residual functional activity of C5. Because this test is available as one of the routine clinical laboratory tests, it would be useful for exploring reasons why some patients do not develop hemolysis with dosing intervals longer than 14 d. 15) Despite these limitations, our data support the hypothesis that an inevitable prolongation of eculizumab dosing interval is associated with breakthrough hemolysis in eculizumab responders.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Recently, Peffault de Latour et al reported the usefulness of a 50% hemolytic complement (CH50) assay for assessing the residual functional activity of C5. Because this test is available as one of the routine clinical laboratory tests, it would be useful for exploring reasons why some patients do not develop hemolysis with dosing intervals longer than 14 d. 15) Despite these limitations, our data support the hypothesis that an inevitable prolongation of eculizumab dosing interval is associated with breakthrough hemolysis in eculizumab responders.…”
Section: Discussionsupporting
confidence: 70%
“…While the reported mean plasma elimination half-life of eculizumab is 11.3±3.4 d, 1) there is a large intra and interindividual variability in eculizumab plasma concentration-time courses in previous clinical trial and some patients exhibited plasma drug concentrations close or lower than the plasma drug levels required to suppress C5 activation. 4,5,15) Recently, Peffault de Latour et al reported obesity (body mass index 29) might have been associated with low plasma eculizumab concentrations (<50 µg/mL) and frequent hemolytic attacks in a patient. 15) However, we found no significant association between body weight of patients and the development of breakthrough hemolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data, therefore, deviate from earlier reports indicating a heterogeneous response to eculizumab treatment with 25-35% of the eculizumab-treated patients still requiring RBC transfusions. (Brodsky, et al, 2008, Luzzatto, et al, 2011, Kelly, et al, 2011 Because these reported suboptimal hematological responses were attributed to either extravascular hemolysis or incomplete C5 blockade, (Hill, et al, 2010, Risitano, et al, 2009, Peffault de Latour, et al, 2015 we assessed hemolysis and complement biomarkers in our PNH patients looking for signs of hemolysis. These analyses demonstrated that despite our patients have not required RBC transfusions, most of them, in agreement with previous reports, present signs of persistent hemolysis (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…(Rondelli, et al, 2014) In addition to this extravascular removal of heavily opsonized PNH-E, one study has recently indicated that the residual low-level hemolysis could, in some patients, be related to incomplete C5 blockade and recommended close supervision of free eculizumab levels and terminal pathway activity to prevent this possibility. (Peffault de Latour, et al, 2015) Here, we searched for correlations between hemolysis parameters, complement determinations (including CR1 H/L genotypes) and plasma levels of free eculizumab in our cohort of eculizumab-treated patients. We show that most eculizumab-treated patients presented signs of low-level hemolysis.…”
Section: Introductionmentioning
confidence: 99%